2015
DOI: 10.1186/s40199-015-0133-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of esomeprazole and omeprazole: Racemate to single enantiomer switch

Abstract: BackgroundBoth omeprazole and its S enantiomer (esomeprazole) have been available and used to treat  symptoms of gastroesophageal reflux disease (GERD) and conditions associated with excessive stomach acid secretion for more than a decade. Controversy exists over improved efficacy of S enantiomer (esomeprazole) over parent racemate (omeprazole). However, a comparison of the clinical outcomes of these products may reveal the rationale for switching from the racemate to single enantiomer. Since enantiomers of om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
0
16
0
3
Order By: Relevance
“…In clinical studies, there is evidence of the OME gastroprotective function at doses of 5 to 40 mg/kg by mechanisms associated with interaction with H2 receptors [57], pH control [58], inhibition of CYP2C19 enzymes [42,43], and histamine blockade [59]. OME in in vivo studies increased prostaglandins and sulfhydryl compounds [60], increased expression of BAX and caspases [61], and AhR and CYP1A expression [41].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…In clinical studies, there is evidence of the OME gastroprotective function at doses of 5 to 40 mg/kg by mechanisms associated with interaction with H2 receptors [57], pH control [58], inhibition of CYP2C19 enzymes [42,43], and histamine blockade [59]. OME in in vivo studies increased prostaglandins and sulfhydryl compounds [60], increased expression of BAX and caspases [61], and AhR and CYP1A expression [41].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…However, pharmacokinetic characteristics of them were difference. Many randomized controlled trials (RCTs) and cohort and case-control studies show that esomeprazole has a higher bioavailability, better clinical efficacy, and treatment capacity for acid-related diseases than omeprazole [46]. Depending on the superior acid control ability and good tolerance, esomeprazole has been widely used to patients with acid-related disease including of stress-ulcer prophylaxis in China.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled trial with head to head comparison between omeprazole and esomeprazole found esomeprazole slightly superior for treatment of gastroesophageal reflux disease. Yet, the same study reported no significant difference for Helicobacter pylori treatment outcome . Esomeprazole (20 mg, for 5 days) showed 90% suppression of gastric acidity, which was only marginally higher compared to 79% suppression achieved by identical dosage of omeprazole .…”
Section: Chirality Of Sulfoxidesmentioning
confidence: 92%